Kickboxing on Theta and Beta-2 waves: unravelling the mind's secrets through QEEG analysis - Rydzik, L.; Wasacz, W.; Ambrozy, T.; Kasicki, K.; Ratkowski, W.; Kopanska, M. (Archives of Budo Science of Martial Arts and Extreme Sports, 2023)
Background & Study Aim: Kickboxing is a sport based on striking with all limbs. The most contact-based variation of the sport is K1 rules. Research shows a deficit in the verification of the brain waves before the fight of the athletes. Therefore, the aim of the present study was to deepen the knowledge of the properties of Theta and Beta-2 brainwaves before a kickboxing fight in the K1 formula.